2022
DOI: 10.3389/fgene.2022.891408
|View full text |Cite
|
Sign up to set email alerts
|

KIF2C is a Biomarker Correlated With Prognosis and Immunosuppressive Microenvironment in Human Tumors

Abstract: Kinesin superfamily member 2C (KIF2C) is an essential regulator of the cell cycle and its aberrant expression can promote tumor progression. However, the mechanism of KIF2C in pan-cancer is unclear.Data were obtained from public databases, including The Cancer Genome Atlas (TCGA), UALCAN, TIMER and CellMiner. The data came from public databases such as The Cancer Genome Atlas (TCGA), UALCAN, TIMER, and CellMiner. We analyzed the correlation of KIF2C with expression, prognosis, tumor mutation burden (TMB), micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Increasing research has revealed the significance of RNA m 6 A methylation in regulating and modulating immune cells [ [53] , [54] , [55] , [56] ]. A previous study showed that KIF2C expression was significantly tumor-associated macrophages (TAMs), which were involved in m 6 A modification [ 57 ]. Also, studies have demonstrated that C1q + TAMs are controlled by the m 6 A program and regulate tumor-infiltrating CD8 + T cells via the expression of numerous immunomodulatory ligands [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing research has revealed the significance of RNA m 6 A methylation in regulating and modulating immune cells [ [53] , [54] , [55] , [56] ]. A previous study showed that KIF2C expression was significantly tumor-associated macrophages (TAMs), which were involved in m 6 A modification [ 57 ]. Also, studies have demonstrated that C1q + TAMs are controlled by the m 6 A program and regulate tumor-infiltrating CD8 + T cells via the expression of numerous immunomodulatory ligands [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…19 Research suggests that the regulation of KIF2C in these tumor cells is disrupted, leading to enhanced mitotic defects and promoting tumor progression. 20 TTK protein kinase (TTK) is a dual-speci city protein kinase with the ability to phosphorylate tyrosine, serine, and threonine residues. It is associated with cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, single cells RNA-seq analysis in HNSCC also revealed that METTL1 knockout could impair direct communication between stromal cells and epithelial cells via inhibition of IL-1b and its receptors 99 . Specific to each subtype, the infiltration of CAFs was demonstrated to be positively correlated with the m7G regulator KIF2C, and eIF4E could promote the oncogenic transformation of fibroblasts by facilitating nuclear export of cyclin D1 mRNAs 71 , 114 . Previous studies revealed that the endothelial cell line HUVEC could be shaped by METTL1.…”
Section: M7g Regulate Time By Affecting Tumor and Stromal Cellsmentioning
confidence: 99%
“…The translation of TGF-β2 was upregulated by METTL1-dependent tRNA m7G modification, which could induce the differentiation of peripheral blood mononuclear cells (PBMCs) into PMN-MDSCs and increase their infiltration, thereby suppress the function of CD8 + T cells and promote HCC progression [76,113]. Moreover, clustering analysis in HCC demonstrated that the m7G modification level positively correlated with abundance of MDSCs in TIME, and some novel regulators such as NUDT16 and KIF2C were involved in MDSCs regulation [114,115]. On the contrary, comprehensive analysis based on m7G-related genes in skin cutaneous melanoma (SKM) suggested the higher overall survival regulated by EIF4E3 and IFIT5, which was associated with more immune infiltration including MDSCs [116].…”
Section: Myeloid-derived Suppressor Cells (Mdscs)mentioning
confidence: 99%